2012
DOI: 10.1212/wnl.0b013e3182605801
|View full text |Cite
|
Sign up to set email alerts
|

Novel late-onset Alzheimer disease loci variants associate with brain gene expression

Abstract: CLU and MS4A4A eSNPs may at least partly explain the LOAD risk association at these loci. CLU and ABCA7 may harbor additional strong eSNPs. These results have implications in the search for functional variants at the novel LOAD risk loci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 33 publications
5
95
2
Order By: Relevance
“…Previous evidence has suggested that the expression of MS4A4A and MS4A6A was increased in the brain tissue of autopsied AD patients [45], confirming the expression of these genes in the cerebellum and frontal cortex and the expression levels that may well be related with disease status also have been found. Another study found that MS4A6A expression levels were associated with Braak tangle and Braak plaque scores and higher level of MS4A6A expression in the parietal lobe was associated with more advanced brain pathology in AD patients [46].…”
Section: The Expression Of Ms4a Gene Cluster In Adsupporting
confidence: 77%
“…Previous evidence has suggested that the expression of MS4A4A and MS4A6A was increased in the brain tissue of autopsied AD patients [45], confirming the expression of these genes in the cerebellum and frontal cortex and the expression levels that may well be related with disease status also have been found. Another study found that MS4A6A expression levels were associated with Braak tangle and Braak plaque scores and higher level of MS4A6A expression in the parietal lobe was associated with more advanced brain pathology in AD patients [46].…”
Section: The Expression Of Ms4a Gene Cluster In Adsupporting
confidence: 77%
“…If the coinheritance between the AD SNP and the functional SNP is modest or if there is more than one functional SNP, discerning an association between the AD SNP and functional changes is especially challenging. Second, genetic expression studies often use microarray data (Guerreiro et al, 2010;Allen et al, 2012) that are often unable to accurately quantify individual mRNA isoforms. Finally, human brain samples are heterogeneous with regard to cell types, and most expression studies do not control for variation in the proportion of cell type.…”
Section: Discussionmentioning
confidence: 99%
“…Clusterin mRNA expression is elevated in AD brains (53, 54) and is detected in amyloid plaques (55, 56). Purified clusterin interacts with Aβ and influences fibril formation in vitro (57-59).…”
Section: Cholesterol Metabolismmentioning
confidence: 99%